2016
DOI: 10.1021/acs.jpcc.6b07592
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Coupling Modulation in n-Alkanethiolate Protected Au25(SR)180 Clusters

Abstract: We have studied, both experimentally and theoretically, the Raman vibrational spectra of a series of n-alkanethiolate protected Au25(SC n H2n+1)18 clusters, with n = 2, 3, 4, 5, 6, 8, 10, 12, and 14. The C–H stretching region of the infrared spectra reveals that, while shorter chains are flexible, longer chains are more ordered with a propensity toward extended all-trans conformation. The different behavior of long and short chains is also reflected in the low-frequency Raman spectra of the clusters, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 52 publications
6
28
0
Order By: Relevance
“…Previous investigation on temperature dependent absorption spectra of Au 38Q reveals that the phonon frequency of the surface -S-Au-S-Au-S-staples is around 400 cm -1 . 37,44 The lower frequencies of phonons for both isomers indicate that the coherent phonons observed here should originate in the Au 23 core. Different phonon frequencies have been reported for gold nanoclusters with different structures.…”
mentioning
confidence: 75%
“…Previous investigation on temperature dependent absorption spectra of Au 38Q reveals that the phonon frequency of the surface -S-Au-S-Au-S-staples is around 400 cm -1 . 37,44 The lower frequencies of phonons for both isomers indicate that the coherent phonons observed here should originate in the Au 23 core. Different phonon frequencies have been reported for gold nanoclusters with different structures.…”
mentioning
confidence: 75%
“…The vibrational study was performed by means of Raman spectroscopy instead of SERS to avoid misleading band assignment, reassuring Raman spectroscopy as a powerful analytical technique that can provide key information on the structure and bonding processes of the adsorbate molecules on metal surfaces in the solid and liquid phase. [4,40,41] The high quality of our Raman spectroscopy data provides very well resolved bands with higher definition than previous SERS results, [34][35][36][37] contrary to what can be expected when studying systems that involve metal surfaces. This quality data allowed us to determine the structural differences that the Au NP metallic surface induces on the cysteine molecule upon adsorption.…”
Section: Introductionmentioning
confidence: 88%
“…Our method produced colloidal neutral clusters in high yield with high affinity to the medium (H 2 O), allowing the attachment of the zwitterionic biosurfactant cysteine on their surface, conferring stability versus aggregation and coalescence that may cause particle growth. The vibrational study was performed by means of Raman spectroscopy instead of SERS to avoid misleading band assignment, reassuring Raman spectroscopy as a powerful analytical technique that can provide key information on the structure and bonding processes of the adsorbate molecules on metal surfaces in the solid and liquid phase . The high quality of our Raman spectroscopy data provides very well resolved bands with higher definition than previous SERS results, contrary to what can be expected when studying systems that involve metal surfaces.…”
Section: Introductionmentioning
confidence: 97%
“…However, when the Raman spectra of cobalt clusters are compared those of monolayer protected thiolated metal clusters several similarities are apparent. [52][53][54][55] Thiol ligands in similar environments or configurations (like staples) should exhibit similar vibrational properties for Co and Au, but the frequencies may be slightly shifted due to different masses and force constants. Raman spectroscopy of gold clusters have focused on the Au-S interface and both experimental and theoretical studies were reported.…”
Section: Structure and Propertiesmentioning
confidence: 99%